A fluorite-structured HfO2/ZrO2/HfO2 superlattice based self-rectifying ferroelectric tunnel junction synapse - Lee, Dong Hyun; Kim, Ji Eun; Cho, Yong Hyeon; Kim, Sojin; Park, Geun Hyeong; Choi, Hyojun; Lee, Sun Young; Kwon, Taegyu; Kim, Da Hyun; Jeong, Moonseek; Jeong, Hyun Woo; Lee, Younghwan; et al. (Royal Society of Chemistry, 2024)
A self-rectifying ferroelectric tunnel junction that employs a HfO2/ZrO2/HfO2 superlattice (HZH SL) combined with Al2O3 and TiO2 layers is proposed. The 6 nm-thick HZH SL effectively suppresses the formation of non-ferroelectric phases while increasing remnant polarization (P-r). This enlarged P-r modulates the energy barrier configuration, consequently achieving a large on/off ratio of 1273 by altering the conduction mechanism from off-state thermal injection to on-state Fowler-Nordheim tunneling. Moreover, the asymmetric Schottky barriers at the top TiN/TiO(2)and bottom HfO2/Pt interfaces enable a self-rectifying property with a rectifying ratio of 1550. Through calculations and simulations it is found that the device demonstrates potential for achieving an integrated array size exceeding 7k while maintaining a 10% read margin, and shows potential for application in artificial synapses for neuromorphic computing with an image recognition accuracy above 92%. Finally, the self-rectifying behavior and device-to-device variation reliability are confirmed in a 9 x 9 crossbar array structure.